Evaluation of Volatile Profile and In Vitro Antioxidant Activity of Fermented Green Tea Infusion With Pleurotus sajor-caju (Oyster Mushroom) - Su, Wei-Ying; Gao, Shu-Yi; Zhan, Si-Jia; Wu, Qi; Chen, Gui-Mei; Han, Jin-Zhi; Lv, Xu-Cong; Rao, Ping-Fan; Ni, Li (Frontiers in Nutrition, 2022)
Although green tea has strong antioxidant activity, it usually has distinct astringency, bitter taste and typical green flavor due to its post-harvest treatment without withering and enzymatic oxidation. Microbial fermentation is a promising strategy to give green tea infusion special taste and flavor mainly because of the metabolic transformation ability of microorganisms. In this study, starter culture of edible mushroom Pleurotus sajor-caju (oyster mushroom) was used for submerged fermentation of green tea infusion in order to improve its flavor and taste quality. The volatile profile determined by headspace solid phase microextraction (HS-SPME) coupled with gas chromatography mass spectrometry (GC-MS) showed that the contents of (Z)-2-penten-1-ol and methyl heptadienone in green tea infusion were decreased significantly by the fermentation with the basidiomycete P. sajor-caju, which would alleviate the astringency and grass flavor of green tea infusion to a certain extent. Meanwile, the contents of linalool and geraniol were increased by 9.3 times and 11.3 times, respectively, while methyl salicylate was newly produced after fermentation by P. sajor-caju, endowing the fermented tea infusion with pleasant flower and fruit aroma. In addition, the polyphenol profile was determined using high performance liquid chromatography equipped with ion trap mass spectrometry (HPLC-MS), and the results indicated that the contents of most polyphenols in green tea infusion decreased significantly after fermentation by P. sajor-caju. Due to the significant reduction of catechins and anthocyanins in fermented green tea infusion, the astringency and bitterness was significantly alleviated. The antioxidant activity of fermented green tea infusion was obviously decreased, especially the DPPH free radical scavenging ability and the ferric reducing power. However, it is noteworthy that the ABTS free radical scavenging ability was improved, compared with the unfermented one, indicating that the increased tea pigments and volatile metabolites (such as linalool and geraniol) after fermentation with P. sajor-caju may also contribute to the antioxidant capacity of fermented green tea infusion. Overall, these findings will provide feasible technical support and innovative approach for the deep processing of low-grade green tea.